Estimation of Ecosystem Services (EESs) loss due to transformation of Local Climatic Zones (LCZs) in Sriniketan-Santiniketan Planning Area (SSPA)West Bengal, India. (May 2019) - Das, Manob; Das, Arijit
Highlights: We examine the local climatic zones (LCZs) changes in Sriniketan-Santiiketan Planning Area (SSPA) from 2000 to 2017. We assessed responses of ecosystem service values (ESVs) to LCZs in SSPA). Ecosystem Services (ESs) degraded by US 1 (−18.73%) million and US 3.50 million (−8.70%) since 2000–2017. The declining trends of ESVs are modest in comparison to global average. Abstract: Accessing the impact of land use/land cover dynamics on the Ecosystem Service Values (ESVs) is necessary for sustainable development at regional and global scale. Estimation of changes in Ecosystem service value (ESV) in response to local climatic zones (LCZs) are performed using GIS technique and corresponding with the global value coefficient for the year 2000 and 2017 in SSPA. Coefficient of Sensitivity (CS) is also used to access the reliability of the estimation process for using the LCZ classes as a proxy with the equivalent biomes. During the study period, the compact low rise (LCZ 3), open low rise (LCZ 6), bare soil/sand (LCZ F2) increased by 22.35%, 23.76% and 0.35% per year. On the other hand cropland (LCZ F1), water (LCZ G) and sparsely built (LCZ 9) decreased by 1.36%, 1.62% and 1.78% per year respectively. The overall result also shows a decreasing trend of total ESV since 2000–2017 from US 1 million and US 3.5 million when value coefficient of 1997 and modified value coefficient of 2014 is applied. The significant changes are also recorded in individual ecosystem service function such as water regulation, water supply, soil formation, nutrient cycling, food production, genetic resource which are the highest contributor to total ESVs for both the unit values used.